2019
DOI: 10.1016/j.molliq.2018.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nickel chrysotile nanotubes tethered with pH-sensitive poly(methacrylic acid) brushes for Cu(II) adsorption

Abstract: Artikkelit Luonnontieteiden ja metsätieteiden tiedekunta 2019 Magnetic nickel chrysotile nanotubes tethered with pH-sensitive poly(methacrylic acid) brushes for Cu(II) adsorption Jiangac, De Bin Elsevier BV Tieteelliset aikakauslehtiartikkelit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The area of peak corresponding to C=O decreased by 14.5%. It was found that the carboxylate groups (COO − ) on the LBC-P-1.3-200-2 could easily adsorb Cd(II) through electrostatic interaction and ion exchange [ 56 ]. The curve-fitted Cd 3d core-level spectrum displayed the Cd(II) complexes at the peaks of 405.36 and 412.07 eV ( Figure 9 d), indicating that the surface groups were bound to Cd(II) successfully.…”
Section: Resultsmentioning
confidence: 99%
“…The area of peak corresponding to C=O decreased by 14.5%. It was found that the carboxylate groups (COO − ) on the LBC-P-1.3-200-2 could easily adsorb Cd(II) through electrostatic interaction and ion exchange [ 56 ]. The curve-fitted Cd 3d core-level spectrum displayed the Cd(II) complexes at the peaks of 405.36 and 412.07 eV ( Figure 9 d), indicating that the surface groups were bound to Cd(II) successfully.…”
Section: Resultsmentioning
confidence: 99%
“…36 However, the Boyd 37 fitted curves (Figure S4) and the corresponding parameters (Table S5) show that the external liquid film diffusion is not the only rate-controlling factor. 38 Consequently, both intraparticle diffusion and external liquid film diffusion have taken place simultaneously in the adsorbing As(V) process. In addition, both the rate constant k id and k fd values of the γ-Fe 2 O 3 @PANI-3 for the two models are much higher than those of γ-Fe 2 O 3 , suggesting the occurrence of a process with a high mass transfer rate for γ-Fe 2 O 3 @PANI-3.…”
Section: Resultsmentioning
confidence: 99%
“…When the adsorbate molecules or adsorbent surfaces are ionizable, it is no doubt that solution pH will significantly affect the adsorption of adsorbents or adsorbates. 48 Considering the inherent pHdependent characteristics of sulfonic groups (−SO 3 − ) in the zwitterionic PSBMA brushes, solution pH can influence the Pb 2+ adsorption amount on the PSBMA-modified sorbents by means of electrostatic interaction and ion exchange. Although solution pH cannot evidently affect the intrinsically positively charged features of quaternary ammonium groups (−NH 4 + ) in the zwitterionic PSBMA brushes, phenol, which is known as carbolic acid with a pK a of 9.95, can exist as an anionic species because of the conjugate base in the aromatic ring being stabilized through resonance, thus adsorbing phenol via ion exchange.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…When the adsorbate molecules or adsorbent surfaces are ionizable, it is no doubt that solution pH will significantly affect the adsorption of adsorbents or adsorbates . Considering the inherent pH-dependent characteristics of sulfonic groups (−SO 3 – ) in the zwitterionic PSBMA brushes, solution pH can influence the Pb 2+ adsorption amount on the PSBMA-modified sorbents by means of electrostatic interaction and ion exchange.…”
Section: Results and Discussionmentioning
confidence: 99%